2019
DOI: 10.1021/acsphotonics.9b01481
|View full text |Cite
|
Sign up to set email alerts
|

Improving Indistinguishability of Single Photons from Colloidal Quantum Dots Using Nanocavities

Abstract: Colloidal quantum dots have garnered active research interest as quantum emitters due to their robust synthesis process and straightforward integration with nanophotonic platforms. However,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
(84 reference statements)
0
24
0
Order By: Relevance
“…These nanocapsules provide a more robust technique to incorporate DBT molecules into nanophotonic structures. Such devices can be used to achieve the high indistinguishably and single-mode collection necessary for using photons from DBT in many quantum information protocols [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…These nanocapsules provide a more robust technique to incorporate DBT molecules into nanophotonic structures. Such devices can be used to achieve the high indistinguishably and single-mode collection necessary for using photons from DBT in many quantum information protocols [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Several SPSs have been identified in the past decades such as quantum dots [28], transition metal dichalcogenides (TMDC) [29], hBN (hexagonal Boron Nitride) [30,31], Nitrogen vacancy in diamonds [32], spontaneous parametric down-conversion in nonlinear crystals etc [33]. Recently, it has been found that the coupling of single photons sources with cavity results in Purcell enhanced indistinguishability [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] It is known that large Purcell enhancements are beneficial for improving the brightness and indistinguishability of single‐photon emitters. [ 18,21–25 ] However, in the above emitter–waveguide systems, [ 7–9 ] the Purcell enhancements were negligible because the optical mode volumes of the corresponding dielectric waveguide modes were much larger than λ 3 . [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%